2021
DOI: 10.3847/1538-4357/abcc6b
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Heating and Solar Wind Formation in Quiet Sun and Coronal Holes: A Unified Scenario

Abstract: Coronal holes (CHs) are darker than the quiet Sun (QS) when observed in coronal channels. This study aims to understand the similarities and differences between CHs and QS in the transition region using the Si iv 1394 Å line, recorded by the Interface Region Imaging Spectrograph, by considering the distribution of magnetic field measured by the Helioseismic and Magnetic Imager on board the Solar Dynamics Observatory. We find that Si iv intensities obtained in CHs are lower than those obtained in QS for regions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 52 publications
5
17
0
Order By: Relevance
“…Bryans et al (2020) found that some CHs may be identified through a marginal excess in the peak separation of the Mg II h line. Similarly, for Si IV line, Tripathi et al (2021) found that CHs and QS show differences in intensities and Doppler shifts for the regions with identical |B|, while no difference in the non-thermal width was observed.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Bryans et al (2020) found that some CHs may be identified through a marginal excess in the peak separation of the Mg II h line. Similarly, for Si IV line, Tripathi et al (2021) found that CHs and QS show differences in intensities and Doppler shifts for the regions with identical |B|, while no difference in the non-thermal width was observed.…”
Section: Introductionmentioning
confidence: 68%
“…The details of the IRIS observations are given in Table . 1. Note that DS1, DS2 and DS5 are the same ones used by Tripathi et al (2021). We use corresponding coordinated AIA data cubes for this study, while the full disk HMI cubes were cut out from Level-2 data.…”
Section: Observations and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Due to such associations and various other properties of the transients, the process of magnetic reconnection is considered to be one of the key mechanisms for their generation. These transients observed ubiquitously throughout the solar atmospheric are further considered to play an essential role in transferring the mass and energy within the solar atmosphere (Parker 1988;Schrijver et al 1997;Moore et al 1999;Winebarger et al 2002;Yamauchi et al 2005;Alipour et al 2012;Priest 2014;) and formation of the solar wind including switchbacks (Hassler et al 1999;Tu et al 2005;Zank et al 2020;Tripathi et al 2021;Liang et al 2021;.…”
Section: Introductionmentioning
confidence: 99%